Insulating tape for new energy battery and preparation method of insulating tape
By combining modified polyimide resin with epoxy resin E-51 crosslinking and modified nano-silica, the problems of high temperature resistance and electrolyte corrosion of new energy tapes have been solved, achieving high safety and long life insulation performance, making them suitable for new energy batteries.
Patent Information
- Application Number
- CN202511392472.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2025-10-31
- Estimated Expiration
- 2045-09-26
AI Technical Summary
Traditional new energy tapes have poor high-temperature resistance, weak resistance to electrolyte corrosion, and insufficient insulation performance, which cannot meet the high safety and long life requirements of power batteries.
A high-density three-dimensional network molecular structure is formed by crosslinking modified polyimide resin with epoxy resin E-51, combined with pretreated glass fiber cloth and modified nano silica. The use of silane coupling agent KH-550 and triethylenetetramine ensures that the fiber cloth is tightly bonded to the resin matrix. A dense physical barrier layer is formed through multi-step modification of modified nano silica, which improves insulation and mechanical properties.
It maintains a stable insulation structure under extreme operating conditions, avoids the risk of short circuits, and retains insulation performance and mechanical strength even after long-term immersion in electrolyte, thereby improving the overall service life and safety of the battery.
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy battery module technology, specifically to an insulating tape for new energy batteries and its preparation method. Background Technology
[0002] Against the backdrop of the rapid development of the new energy industry, the safety, stability and service life of the power battery, as the core energy supply component, are crucial to the performance of the whole vehicle. Insulating tape, as a key insulating and protective material inside the battery, directly affects the reliability of battery operation.
[0003] Currently, most traditional insulating tapes on the market use ordinary resin as the base material, combined with a single filler, which has obvious performance shortcomings. On the one hand, traditional resins have insufficient high-temperature resistance. During the charging and discharging process of power batteries, the internal temperature of the battery is prone to generate heat of 40-80°C due to chemical reactions, and under some extreme conditions, the temperature may even exceed 100°C. At this time, ordinary insulating tape is prone to softening and deformation, leading to insulation layer failure and causing the risk of internal short circuits in the battery. On the other hand, the electrolyte inside the battery is highly corrosive. When the resin matrix of traditional tape comes into contact with the electrolyte, it is prone to swelling and degradation, resulting in decreased tape adhesion, delamination, and further damage to the insulation structure.
[0004] Meanwhile, the fillers silica and calcium carbonate in traditional insulating tapes have poor dispersibility and tend to agglomerate in the substrate. This not only fails to improve the mechanical and insulation properties of the tape but also creates localized weak points, reducing the overall protective effect of the tape. In addition, some insulating tapes use substrates such as ordinary cotton cloth and polyester film with low mechanical strength. During battery assembly and long-term use, they are easily damaged by external pressure and vibration, making it impossible to maintain a stable insulation and protective state over a long period.
[0005] These problems severely restrict the safety and lifespan of power batteries, failing to meet the "high safety, long lifespan, and resistance to harsh working conditions" requirements of new energy vehicles for power batteries. Therefore, developing an insulating tape for new energy batteries that is resistant to high temperatures and electrolyte corrosion, has stable insulation performance, and excellent mechanical properties has become a key issue that the industry urgently needs to solve. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides an insulating tape for new energy batteries and its preparation method, solving the problems of insufficient insulation performance, poor high-temperature resistance, and weak electrolyte resistance of traditional new energy tapes.
[0007] To achieve the above objectives, the present invention provides the following technical solution: An insulating tape for new energy batteries is prepared by coating a pretreated glass fiber cloth with a coating material. The coating material contains the following raw materials in parts by weight: 15-20 parts modified polyimide resin, 2-4 parts epoxy resin E-51, 71-77 parts ethanol / butanone mixed solvent, 3-5 parts modified nano silica, 0.2-0.4 parts silane coupling agent KH-550, 0.1-0.3 parts polydimethylsiloxane, 0.1-0.2 parts paraffinic mineral oil, and 0.3-0.5 parts triethylenetetramine; the glass fiber cloth pretreatment material contains deionized water and a 5%-8% sodium hydroxide solution.
[0008] Furthermore, the volume ratio of ethanol to butanone in the ethanol / butanone mixed solvent is 3:1.
[0009] Furthermore, the modified nano-silica is prepared using the following specific steps: A1. Take nano-silica, add deionized water, stir at 300 rpm and ultrasonically disperse for 30-40 min to promote dispersion of nano-silica, add 0.1 mol / L hydrochloric acid to adjust pH to 4.0-4.5, then add polyvinyl alcohol-1788, stir at 500 rpm until dissolved, heat to 55-65℃ and stir for 1 h, then slowly add silane coupling agent KH-570, keep warm and stir for 5-6 h to introduce organic functional groups and initially improve compatibility with resin; after the reaction is completed, let stand. For 2 hours, sufficient time is provided for the hydrolyzed silanol groups to adsorb onto the hydroxyl groups on the surface of nano-silica via hydrogen bonding, and for the adsorbed intermediates to undergo further dehydration condensation to form stable covalent bonds. This provides enough time to complete the grafting stage of organic groups onto the surface of nano-silica, ensuring that the silane coupling agent binds to the surface of nano-silica to the maximum extent and avoiding the defect of incomplete modification. After centrifugation, the precipitate is first washed with deionized water until neutral, then washed twice with ethanol, and then vacuum dried at 85-95℃ for 7-9 hours to obtain the first modified nano-silica. A2. Take the first modified nano-silica, add anhydrous ethanol, stir and ultrasonically disperse at 300 r / min for 25-35 min, then add azobisisobutyronitrile and continue stirring and ultrasonication for 5-10 min. Under nitrogen protection, heat to 75-85℃, slowly add acrylic acid dropwise, and after the dropwise addition is complete, keep the reaction at 500 r / min for 7-8 h to achieve acrylic acid grafting, further enhance the organic-friendly phase characteristics, and reduce agglomeration. After the reaction is completed, cool naturally to room temperature, filter, wash 5 times with anhydrous ethanol, and then vacuum dry at 100-110℃ for 5-7 h to obtain the second modified nano-silica. A3. Take the second modified nano-silica, add deionized water, stir at 300 r / min and ultrasonically disperse for 20-30 min, then add aluminum chloride and stir until dissolved. Next, slowly add 25% ammonia water to adjust the pH to 7.5-8.0, stir at 500 r / min at room temperature for 3-4 h to form an aluminum chloride coating layer, construct a physical barrier layer, and improve the resistance to electrolyte. After the reaction is completed, centrifuge to separate the precipitate, wash the precipitate with deionized water until no white precipitate is added to the washing liquid with silver nitrate solution, and then vacuum dry at 90-100℃ for 6-8 h to obtain modified nano-silica.
[0010] Furthermore, the ratio of nano-silica, deionized water, polyvinyl alcohol-1788, and silane coupling agent KH-570 in A1 is 400-500g: 800-1000ml: 20-30g: 25-35ml.
[0011] Furthermore, the ratio of the first modified nano-silica, anhydrous ethanol, azobisisobutyronitrile, and acrylic acid in A2 is 300-350g: 700-800ml: 0.8-1.5g: 25-35g.
[0012] Furthermore, the ratio of the second modified nano-silica, deionized water, and aluminum chloride in A3 is 250-300g: 600-700ml: 12-18g.
[0013] Furthermore, the modified polyimide resin is prepared using the following specific steps: B1. Add N,N-dimethylformamide to a four-necked flask, and under nitrogen protection, add m-phenylenediamine and 4,4'-diaminodiphenyl ether. Stir at 400 r / min until dissolved, and control the temperature at 0-5℃. Add pyromellitic dianhydride in 3-4 portions, stirring for 30-40 min after each addition to avoid excessive local reaction. After the viscosity of the system reaches 5000-8000 mPa·s, continue stirring and reacting for 2-3 h to obtain a copolymer polyamic acid solution. B2. Add xylene to the copolymerized polyamic acid solution and stir at 500 r / min to form a homogeneous mixture. Add maleic anhydride and dicumyl peroxide, and heat to 85-95℃ under nitrogen protection. Stir and reflux for 4-5 h. After the reaction is complete, heat to 120-130℃ and stir at 300 r / min for 2-3 h to imidize, completing the imidization process, constructing a grafted structure, and improving thermal stability. After cooling to room temperature, filter, wash three times with xylene, and then vacuum dry at 120-130℃ for 6-8 h to obtain the grafted modified polyimide resin. B3. Take the grafted modified polyimide resin and add a 3:1 volume ratio of ethanol / butanone mixed solvent. Stir at 400 r / min until dissolved. Add epoxy resin E-51 and triethylenetetramine. Stir at 500 r / min until homogeneous, then heat to 60-70℃ and stir for 3-4 hours. During this period, take a sample every 1 hour to measure the gel time. Stop the reaction when the gel time stabilizes at 30-40 minutes to ensure appropriate crosslinking degree. Pour the solution into water to precipitate, filter, wash 3 times with ethanol, and vacuum dry the precipitate at 130-140℃ for 7-9 hours to obtain the modified polyimide resin.
[0014] Furthermore, the ratio of N,N-dimethylformamide, m-phenylenediamine, 4,4'-diaminodiphenyl ether, and pyromellitic dianhydride in B1 is 200-250ml: 30-40g: 15-20g: 40-50g.
[0015] Furthermore, the ratio of the amount of the copolymer polyamic acid solution, xylene, maleic anhydride, and dicumyl peroxide in B2 is 300-350ml: 500-600ml: 8-12g: 0.5-1g.
[0016] Furthermore, the ratio of grafted modified polyimide resin, ethanol / butanone mixed solvent, epoxy resin E-51, and triethylenetetramine in B3 is 120-150g: 400-500ml: 15-20g: 2-3g.
[0017] A method for preparing insulating tape for new energy batteries specifically includes the following steps: S1. Place the fiberglass cloth in deionized water and stir at 300 rpm for 15 minutes to remove surface dust and loose fibers. Drain the cloth. Transfer it to a 5%-8% sodium hydroxide solution and stir at 200 rpm for 20 minutes at 60-70°C to activate the cloth surface and generate hydroxyl active sites. Wash with deionized water until the pH is neutral. Then dry the cloth in an oven at 120-130°C for 2-3 hours and cool it for later use. This creates conditions for subsequent bonding with coatings and avoids impurities or moisture affecting the adhesion and insulation of the tape. S2. Take the modified polyimide resin and epoxy resin E-51, add them to the ethanol / butanone mixed solvent, and stir at 400-600 r / min at 50-60℃ to promote the complete dissolution of the modified polyimide resin and epoxy resin E-51 to form a clear resin liquid, so as to avoid uneven coating caused by undissolved raw materials. S3. Take the modified nano-silica, add the ethanol / butanone mixed solvent and silane coupling agent KH-550, stir at 800 r / min for 15 min, and then ultrasonically disperse for 10-15 min for pretreatment; then slowly add the pretreated modified nano-silica to the resin solution in S2, stirring at 1000-1200 r / min while adding, and continue high-speed stirring for 25-35 min after the addition is complete, and then transfer to an ice-water bath environment for ultrasonic dispersion for 20-30 min to ensure that the nano-silica does not agglomerate; the pretreated and dispersed modified nano-silica, the high-speed stirring and low-temperature ultrasonication work together to thoroughly break the agglomerates and ensure uniform dispersion in the resin solution, and stir for 30 s every 5 min to further enhance the dispersion effect; S4. Add polydimethylsiloxane and paraffinic mineral oil to the S3 dispersion system, adjust the stirring speed to 300-400 r / min to avoid introducing air bubbles at high speed, and stir at room temperature for 15-25 min to ensure uniform dispersion of the additives; introduce nitrogen gas, slowly add triethylenetetramine to the system, and stir at 300-400 r / min for 15-20 min to ensure that the curing agent is completely integrated and there are no obvious particles or stratification; S5. Filter the prepared coating through an 800-1000 mesh nylon filter. Let the filtered coating stand at room temperature for 30-60 minutes to naturally remove the residual micro bubbles in the system, and obtain an insulating tape coating that can be used for coating. S6. Lay the pretreated fiberglass cloth flat on the conveyor belt of the coating machine, and evenly coat both sides of the cloth with the above coating, with a coating thickness of 0.05-0.1mm. After coating, send the substrate into the drying oven and process it according to the step curing procedure: first dry at 90-95℃ for 25-35min, then raise the temperature to 125-135℃ for 55-65min, and finally raise the temperature to 175-185℃ for 110-130min to fully complete the curing reaction, ensuring the tape's high temperature resistance and electrolyte resistance, and obtain the insulating tape for new energy batteries.
[0018] Furthermore, in S3, the temperature of the ice-water bath environment is controlled at 0-5℃, the ultrasonic dispersion power is 300-500W, and the mixture is stirred once every 5 minutes during the ultrasonic process, with each stirring lasting 30 seconds, in order to further prevent the agglomeration of modified nano-silica.
[0019] Furthermore, in S6, the coating speed of the coating machine is 1-2 m / min, and hot air is used for drying during the coating process. The hot air temperature is 40-50℃ and the hot air speed is 1-1.5 m / s to prevent uneven thickness of the coating due to sagging during the coating process, and at the same time, to initially remove some of the solvent.
[0020] This invention provides an insulating tape for new energy batteries and its preparation method, which has the following beneficial effects: 1. This invention constructs a high-density three-dimensional network molecular structure through the synergistic crosslinking of modified polyimide resin and epoxy resin E-51. After grafting maleic anhydride onto the modified polyimide resin and copolymerizing it with epoxy resin, a large number of heat-resistant aromatic rings and crosslinking sites are introduced into the molecular chain. Combined with triethylenetetramine as a curing agent, this further strengthens the intermolecular bonding force. Simultaneously, after activation with sodium hydroxide, the pretreated glass fiber cloth forms hydroxyl active sites on its surface, which can chemically bond with the silane coupling agent KH-550 in the coating, resulting in a tight bond between the fiber cloth and the resin matrix. This dual structural design of "resin crosslinking + substrate bonding" allows the insulating tape to maintain a stable shape after curing at 175-185℃. Even under extreme charging and discharging conditions of power batteries, it will not soften, deform, or delaminate, maintaining a complete insulation structure over a long period and effectively avoiding the risk of short circuits caused by high temperatures.
[0021] 2. On the one hand, after three-step modification—KH-570 coupling, acrylic acid grafting, and aluminum chloride coating—modified nano-silica forms functional groups with an organic-phase on its surface. These groups can be uniformly dispersed in the resin matrix, filling the tiny gaps between resin molecules and forming a dense physical barrier layer that prevents corrosive ions in the electrolyte from penetrating. On the other hand, in the molecular chain structure of the modified polyimide resin, the chemically resistant imide rings crosslink with the epoxy groups of the epoxy resin, further reducing the hydrophilicity of the resin matrix and the swelling properties of the electrolyte, preventing swelling and degradation of the tape after contact with the electrolyte. With this dual protection, the insulating tape maintains stable insulation performance and mechanical strength even after long-term immersion in battery electrolyte, significantly reducing tape failure caused by electrolyte corrosion and indirectly extending the overall service life of the power battery.
[0022] 3. In terms of insulation performance, the uniform dispersion of modified nano-silica not only fills the microscopic gaps in the resin matrix, but its own high insulation properties also reduce the local conductive paths inside the tape. Combined with the excellent insulation properties of the modified polyimide resin itself, the overall volume resistivity of the tape is greatly improved, effectively blocking the risk of leakage between different electrodes inside the battery. In terms of mechanical properties, the mechanical strength of the glass fiber cloth is retained after pretreatment, and the bonding force with the resin matrix is significantly enhanced, forming a composite structure of "fiber reinforcement-resin bonding". This gives the tape excellent tensile and tear resistance. During battery assembly, even if subjected to external pressure, winding or vibration, it is not easy to break or fracture. In long-term use, it can also resist the stress impact caused by the deformation of the internal structure of the battery, and continuously maintain a stable insulation protection effect, providing dual safety protection for battery assembly and long-term operation.
[0023] 4. During the preparation process, the modified nano-silica is first pretreated with a mixed solvent of ethanol / butanone and silane coupling agent KH-550, and then dispersed by high-speed stirring and ultrasonic dispersion in an ice-water bath. This effectively avoids the agglomeration of nanoparticles and ensures their uniform distribution in the resin solution. Simultaneously, during coating preparation, a stepped stirring rate is adjusted, combined with filtration through an 800-1000 mesh nylon filter and room temperature settling to remove bubbles, resulting in a uniform coating texture free of impurities and bubbles. This uniform coating system, combined with a stable coating speed of 1-2 m / min and hot air-assisted drying, ensures that the coating forms a uniform thickness on both sides of the fiberglass cloth, avoiding localized performance weaknesses caused by uneven coating thickness. Ultimately, this achieves high consistency in product performance during mass production, reduces the defect rate during production, and enhances the value for industrial applications. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1: Preparation of insulating tape for new energy batteries. The specific preparation steps are as follows: S1. Place the fiberglass cloth in deionized water and stir at 300 r / min for 15 min to remove surface dust and loose fibers. Drain the cloth. Transfer it to a 5% sodium hydroxide solution and stir at 200 r / min for 20 min at 60°C to activate the cloth surface. Wash with deionized water until the pH is neutral. Then dry in an oven at 120°C for 2 h and cool for later use. S2. Take 15 parts of polyimide resin and 2 parts of epoxy resin E-51, add them to 70 parts of ethanol / butanone mixed solvent, and stir at 400 r / min at 50℃ until the resin is completely dissolved to form a clear and transparent resin liquid. S3. Take 3 parts of nano-silica, add 1 part of ethanol / butanone mixed solvent and 0.2 parts of silane coupling agent KH-550, stir at 800 r / min for 15 min, and then ultrasonically disperse for 10 min for pretreatment; then slowly add the pretreated nano-silica to the resin solution in S2, stirring at 1000 r / min while adding, and continue high-speed stirring for 25 min after the addition is complete, and then transfer to an ice-water bath environment for ultrasonic dispersion for 20 min, with the temperature controlled at 0℃, the ultrasonic dispersion power is 300W, and stirring is performed once every 5 min during the ultrasonic process, with each stirring lasting 30 s, to ensure that the nano-silica does not agglomerate; S4. Add 0.1 parts of polydimethylsiloxane and 0.1 parts of paraffinic mineral oil to the S3 dispersion system, adjust the stirring speed to 300 r / min, and stir at room temperature for 15 min to ensure uniform dispersion of the additives; introduce nitrogen gas, slowly add 0.3 parts of triethylenetetramine to the system, and stir at 300 r / min for 15 min to ensure that the curing agent is completely integrated and there are no obvious particles or stratification. S5. Filter the prepared coating through an 800-mesh nylon filter. Let the filtered coating stand at room temperature for 30 minutes to naturally remove the residual micro bubbles in the system, and obtain an insulating tape coating that can be used for coating. S6. Lay the pretreated fiberglass cloth flat on the conveyor belt of the coating machine, and evenly coat both sides of the cloth with the above coating at a coating speed of 1m / min. During the coating process, hot air is used to assist drying at a temperature of 40℃ and a speed of 1m / s. The coating thickness is 0.05mm. After coating, the substrate is sent into the drying oven and treated according to the step curing procedure: first, dry at 90℃ for 25min, then raise the temperature to 125℃ for 55min, and finally raise the temperature to 175℃ for 110min to fully complete the curing reaction and ensure the tape's high temperature resistance and electrolyte resistance, thus obtaining the insulating tape for new energy batteries.
[0026] Example 2: Preparation of insulating tape for new energy batteries. The specific preparation steps are as follows: S1. Place the fiberglass cloth in deionized water and stir at 300 r / min for 15 min to remove surface dust and loose fibers. Drain the cloth and transfer it to an 8% sodium hydroxide solution. Stir at 200 r / min at 70°C for 20 min to activate the cloth surface. Wash with deionized water until the pH is neutral. Then dry the cloth in an oven at 130°C for 3 h and cool it for later use. S2. Take 20 parts of polyimide resin and 4 parts of epoxy resin E-51, add them to 75 parts of ethanol / butanone mixed solvent, and stir at 600 r / min at 60℃ until the resin is completely dissolved to form a clear and transparent resin liquid. S3. Take 5 parts of nano-silica, add 2 parts of ethanol / butanone mixed solvent and 0.4 parts of silane coupling agent KH-550, stir at 800 r / min for 15 min, and then ultrasonically disperse for 15 min for pretreatment; then slowly add the pretreated nano-silica to the resin solution in S2 while stirring at 1200 r / min. After the addition is complete, continue to stir at high speed for 35 min, and then transfer to an ice-water bath environment for ultrasonic dispersion for 30 min. The temperature is controlled at 5℃, the ultrasonic dispersion power is 500W, and the stirring is performed once every 5 min during the ultrasonic process. Each stirring time is 30 s to ensure that the nano-silica does not agglomerate. S4. Add 0.3 parts of polydimethylsiloxane and 0.2 parts of paraffinic mineral oil to the S3 dispersion system, adjust the stirring speed to 400 r / min, and stir at room temperature for 25 min to ensure uniform dispersion of the additives; introduce nitrogen gas, slowly add 0.5 parts of triethylenetetramine to the system, and stir at 400 r / min for 20 min to ensure that the curing agent is completely integrated and there are no obvious particles or stratification. S5. Filter the prepared coating through a 1000-mesh nylon filter. Let the filtered coating stand at room temperature for 60 minutes to naturally remove the residual micro bubbles in the system, and obtain an insulating tape coating that can be used for coating. S6. Lay the pretreated fiberglass cloth flat on the conveyor belt of the coating machine, and evenly coat both sides of the cloth with the above coating at a coating speed of 2m / min. During the coating process, hot air is used to assist drying at a temperature of 50℃ and a speed of 1.5m / s. The coating thickness is 0.1mm. After coating, the substrate is sent into the drying oven and treated according to the step curing procedure: first, dry at 95℃ for 35min, then raise the temperature to 135℃ for 65min, and finally raise the temperature to 185℃ for 130min to fully complete the curing reaction and ensure the tape's high temperature resistance and electrolyte resistance, thus obtaining the insulating tape for new energy batteries.
[0027] Example 3: Preparation of insulating tape for new energy batteries. The specific preparation steps are as follows: S1. Place the fiberglass cloth in deionized water and stir at 300 r / min for 15 min to remove surface dust and loose fibers. Drain the cloth. Transfer it to a 6% sodium hydroxide solution and stir at 200 r / min for 20 min at 65°C to activate the cloth surface. Wash with deionized water until the pH is neutral. Then dry in an oven at 125°C for 2.5 h and cool for later use. S2. Take 17 parts of polyimide resin and 3 parts of epoxy resin E-51, add them to 72 parts of ethanol / butanone mixed solvent, and stir at 500 r / min at 55℃ until the resin is completely dissolved to form a clear and transparent resin liquid. S3. Take 4 parts of nano-silica, add 1 part of ethanol / butanone mixed solvent and 0.3 parts of silane coupling agent KH-550, stir at 800 r / min for 15 min, and then ultrasonically disperse for 13 min for pretreatment; then slowly add the pretreated nano-silica to the resin solution in S2 while stirring at 1100 r / min. After the addition is complete, continue to stir at high speed for 30 min, and then transfer to an ice-water bath environment for ultrasonic dispersion for 25 min. The temperature is controlled at 2℃ and the ultrasonic dispersion power is 400W. Stir once every 5 min during the ultrasonic process, and each stirring time is 30s to ensure that the nano-silica does not agglomerate. S4. Add 0.2 parts of polydimethylsiloxane and 0.15 parts of paraffinic mineral oil to the S3 dispersion system, adjust the stirring speed to 350 r / min, and stir at room temperature for 20 min to ensure uniform dispersion of the additives; introduce nitrogen gas, slowly add 0.4 parts of triethylenetetramine to the system, and stir at 350 r / min for 17 min to ensure that the curing agent is completely integrated and there are no obvious particles or stratification. S5. Filter the prepared coating through a 900-mesh nylon filter. Let the filtered coating stand at room temperature for 45 minutes to naturally remove the residual micro bubbles in the system, and obtain an insulating tape coating that can be used for coating. S6. Lay the pretreated fiberglass cloth flat on the conveyor belt of the coating machine, and evenly coat both sides of the cloth with the above coating at a coating speed of 1.5 m / min. During the coating process, hot air is used to assist drying at a temperature of 45°C and a wind speed of 1.2 m / s. The coating thickness is 0.08 mm. After coating, the substrate is sent into the drying oven and treated according to the step curing procedure: first, dry at 92°C for 30 min, then raise the temperature to 130°C for 60 min, and finally raise the temperature to 180°C for 120 min to fully complete the curing reaction and ensure the tape's high temperature resistance and electrolyte resistance, thus obtaining the insulating tape for new energy batteries.
[0028] Example 4: Preparation of modified nano-silica. The specific preparation steps are as follows: A1. Take 400g of nano-silica, add 800ml of deionized water, stir at 300r / min and ultrasonically disperse for 30min, add 0.1mol / L hydrochloric acid to adjust the pH to 4.0, then add 20g of polyvinyl alcohol-1788, stir at 500r / min until dissolved, heat to 55℃ and stir for 1h, then slowly add 25ml of silane coupling agent KH-570, keep warm and stir for 5h; after the reaction is completed, let stand for 2h and then centrifuge to separate the precipitate. Wash the precipitate with deionized water until neutral, then wash it twice with ethanol, and dry it under vacuum at 85℃ for 7h to obtain the first modified nano-silica. A2. Take 300g of the first-modified nano-silica, add 700ml of anhydrous ethanol, stir and ultrasonically disperse at 300r / min for 25min, then add 0.8g of azobisisobutyronitrile and continue stirring and ultrasonication for 5min. Under nitrogen protection, heat to 75℃, slowly add 25g of acrylic acid, and after the addition is complete, keep the temperature at 500r / min for 7h. After the reaction is completed, cool naturally to room temperature and filter. Wash 5 times with anhydrous ethanol, and then vacuum dry at 100℃ for 5h to obtain the second-modified nano-silica. A3. Take 250g of the second modified nano-silica, add 600ml of deionized water, stir at 300r / min and ultrasonically disperse for 20min, then add 12g of aluminum chloride and stir until dissolved. Then slowly add 25% ammonia water to adjust the pH to 7.5, and stir at 500r / min at room temperature for 3h. After the reaction is completed, centrifuge and separate the precipitate. Wash the precipitate with deionized water until no white precipitate is added to the washing liquid with silver nitrate solution. Then vacuum dry at 90℃ for 6h to obtain modified nano-silica.
[0029] Example 5: Preparation of modified nano-silica. The specific preparation steps are as follows: A1. Take 500g of nano-silica, add 1000ml of deionized water, stir at 300r / min and ultrasonically disperse for 40min, add 0.1mol / L hydrochloric acid to adjust the pH to 4.5, then add 30g of polyvinyl alcohol-1788, stir at 500r / min until dissolved, heat to 65℃ and stir for 1h, then slowly add 35ml of silane coupling agent KH-570, keep warm and stir for 6h; after the reaction is completed, let stand for 2h and then centrifuge to separate the precipitate. Wash the precipitate with deionized water until neutral, then wash it twice with ethanol, and dry it under vacuum at 95℃ for 9h to obtain the first modified nano-silica. A2. Take 350g of the first modified nano-silica, add 800ml of anhydrous ethanol, stir and ultrasonically disperse at 300r / min for 35min, then add 1.5g of azobisisobutyronitrile and continue stirring and ultrasonication for 10min. Under nitrogen protection, heat to 85℃, slowly add 35g of acrylic acid, and after the addition is complete, keep the temperature at 500r / min for 8h. After the reaction is completed, cool naturally to room temperature and filter. Wash 5 times with anhydrous ethanol, and then vacuum dry at 110℃ for 7h to obtain the second modified nano-silica. A3. Take 300g of the second modified nano-silica, add 700ml of deionized water, stir at 300r / min and ultrasonically disperse for 30min, then add 18g of aluminum chloride and stir until dissolved. Then slowly add 25% ammonia water to adjust the pH to 8.0, and stir at 500r / min at room temperature for 4h. After the reaction is completed, centrifuge and separate the precipitate. Wash the precipitate with deionized water until no white precipitate is added to the washing liquid with silver nitrate solution. Then vacuum dry at 100℃ for 8h to obtain modified nano-silica.
[0030] Example 6: Preparation of modified polyimide resin. The specific preparation steps are as follows: B1. Add 200 ml of N,N-dimethylformamide to a four-necked flask, and under nitrogen protection, add 30 g of m-phenylenediamine and 15 g of 4,4'-diaminodiphenyl ether. Stir at 400 r / min until dissolved, and control the temperature at 0℃. Add 40 g of pyromellitic dianhydride in three portions, stirring for 30 min after each addition. When the viscosity of the system reaches 5000 mPa·s, continue stirring and reacting for 2 h to obtain a copolymer polyamic acid solution. B2. Add 500 ml of xylene to 300 ml of copolymerized polyamic acid solution and stir at 500 r / min to form a mixed system; add 8 g of maleic anhydride and 0.5 g of dicumyl peroxide, heat to 85 °C under nitrogen protection, and stir under reflux for 4 h; after the reaction is completed, heat to 120 °C and stir at 300 r / min for imidization for 2 h to complete the imidization process; after cooling to room temperature, filter, wash 3 times with xylene, and then vacuum dry at 120 °C for 6 h to obtain grafted modified polyimide resin; B3. Take 120g of grafted modified polyimide resin, add 400ml of ethanol / butanone mixed solvent with a volume ratio of 3:1, and stir at 400r / min until dissolved; add 15g of epoxy resin E-51 and 2g of triethylenetetramine, stir at 500r / min until uniform, then heat to 60℃ and stir and keep warm for 3h. During this period, take samples every 1h to measure the gel time. Stop the reaction when the gel time stabilizes at 30min; pour the solution into water to precipitate, filter, wash 3 times with ethanol, and dry the precipitate under vacuum at 130℃ for 7h to obtain modified polyimide resin.
[0031] Example 7: Preparation of modified polyimide resin. The specific preparation steps are as follows: B1. Add 250 ml of N,N-dimethylformamide to a four-necked flask, and under nitrogen protection, add 40 g of m-phenylenediamine and 20 g of 4,4'-diaminodiphenyl ether. Stir at 400 r / min until dissolved, and control the temperature at 5 °C. Add 50 g of pyromellitic dianhydride in four portions, stirring for 40 min after each addition. When the viscosity of the system reaches 8000 mPa·s, continue stirring and reacting for 3 h to obtain a copolymer polyamic acid solution. B2. Add 600 ml of xylene to 350 ml of copolymerized polyamic acid solution and stir at 500 r / min to form a mixed system; add 12 g of maleic anhydride and 1 g of dicumyl peroxide, heat to 95 °C under nitrogen protection, and stir under reflux for 5 h; after the reaction is completed, heat to 130 °C and stir at 300 r / min for imidization for 3 h to complete the imidization process; after cooling to room temperature, filter, wash 3 times with xylene, and then vacuum dry at 130 °C for 8 h to obtain grafted modified polyimide resin; B3. Take 150g of grafted modified polyimide resin, add 500ml of ethanol / butanone mixed solvent with a volume ratio of 3:1, and stir at 400r / min until dissolved; add 20g of epoxy resin E-51 and 3g of triethylenetetramine, stir at 500r / min until uniform, then heat to 70℃ and stir and keep warm for 4h. During this period, take a sample every 1h to measure the gel time. Stop the reaction when the gel time stabilizes at 40min; pour the solution into water to precipitate, filter, wash 3 times with ethanol, and dry the precipitate under vacuum at 140℃ for 9h to obtain modified polyimide resin.
[0032] Comparative Example 1: Preparation of insulating tape for new energy batteries. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the nano-silica in Example 3 is replaced with the modified nano-silica prepared in Example 4 to prepare insulating tape for new energy batteries.
[0033] Comparative Example 2: Preparation of insulating tape for new energy batteries. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the polyimide resin in Example 3 is replaced with the modified polyimide resin prepared in Example 7 to prepare insulating tape for new energy batteries.
[0034] Comparative Example 3: Preparation of insulating tape for new energy batteries. The specific preparation steps are as follows: The remaining steps remain unchanged, except that the nano-silica in Example 3 is replaced with the modified nano-silica prepared in Example 4, and the polyimide resin is replaced with the modified polyimide resin prepared in Example 7, to prepare the insulating tape for new energy batteries.
[0035] Performance testing ; Based on the performance test results, the insulating tapes for new energy batteries in Examples 1-3 all possess certain volume resistivity, electrolyte resistance, tensile strength, and temperature resistance, and their overall performance shows a trend of gradual improvement with optimization of raw material ratios and process parameters. Comparative Examples 1-3, by replacing the original materials with modified nano-silica and modified polyimide resin, exhibit significantly better performance in all aspects than the examples. Comparative Example 3, using both modified nano-silica and modified polyimide resin, demonstrates the best performance, with volume resistivity at room temperature and high temperature, and volume resistivity after electrolyte resistance, reaching 2.8 × 10⁻⁶. 15 Ω·cm, 2.1×10 15 Ω·cm, 2.6×10 15With an Ω·cm resistance, an electrolyte mass change rate of only +0.7%, a tensile strength retention rate of 98% after electrolyte resistance, a tensile strength of 35.6MPa, a heat distortion temperature of 190℃, and a flame retardant rating of V-0, these properties fully demonstrate the synergistic effect of modified nano-silica and modified polyimide resin, which can significantly improve the insulation, electrolyte resistance, mechanical properties, and high-temperature resistance of the insulating tape.
[0036] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. An insulating tape for new energy batteries, characterized in that: This insulating tape for new energy batteries is prepared by coating pretreated glass fiber cloth with a coating material. The coating material contains the following raw materials by weight: 15-20 parts modified polyimide resin, 2-4 parts epoxy resin E-51, 71-77 parts ethanol / butanone mixed solvent, 3-5 parts modified nano silica, 0.2-0.4 parts silane coupling agent KH-550, 0.1-0.3 parts polydimethylsiloxane, 0.1-0.2 parts paraffinic mineral oil, and 0.3-0.5 parts triethylenetetramine. The glass fiber cloth pretreatment material contains deionized water and 5%-8% sodium hydroxide solution.
2. The insulating tape for new energy batteries according to claim 1, characterized in that: The volume ratio of ethanol to butanone in the ethanol / butanone mixed solvent is 3:
1.
3. The insulating tape for new energy batteries according to claim 1, characterized in that: The modified nano-silica is prepared using the following specific steps: A1. Take nano-silica, add deionized water, stir at 300 r / min and ultrasonically disperse for 30-40 min, add 0.1 mol / L hydrochloric acid to adjust the pH to 4.0-4.5, then add polyvinyl alcohol-1788, stir at 500 r / min until dissolved, heat to 55-65℃ and stir for 1 h, then slowly add silane coupling agent KH-570, keep warm and stir for 5-6 h; after the reaction is completed, let stand for 2 h and then centrifuge to separate the precipitate. Wash the precipitate with deionized water until neutral, then wash it twice with ethanol, and vacuum dry at 85-95℃ for 7-9 h to obtain the first modified nano-silica; A2. Take the first modified nano-silica, add anhydrous ethanol, stir and ultrasonically disperse at 300 r / min for 25-35 min, then add azobisisobutyronitrile and continue stirring and ultrasonication for 5-10 min. Under nitrogen protection, heat to 75-85℃, slowly add acrylic acid dropwise, and after the dropwise addition is complete, keep the reaction at 500 r / min for 7-8 h. After the reaction is completed, cool naturally to room temperature and filter. Wash with anhydrous ethanol 5 times, and then vacuum dry at 100-110℃ for 5-7 h to obtain the second modified nano-silica. A3. Take the second modified nano-silica, add deionized water, stir at 300 r / min and ultrasonically disperse for 20-30 min, then add aluminum chloride and stir until dissolved. Next, slowly add 25% ammonia water to adjust the pH to 7.5-8.0, and stir at 500 r / min at room temperature for 3-4 h. After the reaction is complete, centrifuge and separate the precipitate. Wash the precipitate with deionized water until no white precipitate is added to the washing liquid with silver nitrate solution. Then vacuum dry at 90-100℃ for 6-8 h to obtain modified nano-silica.
4. The insulating tape for new energy batteries according to claim 3, characterized in that: The ratio of nano-silica, deionized water, polyvinyl alcohol-1788, and silane coupling agent KH-570 in A1 is 400-500g: 800-1000ml: 20-30g: 25-35ml; The ratio of the first modified nano-silica, anhydrous ethanol, azobisisobutyronitrile, and acrylic acid in A2 is 300-350g: 700-800ml: 0.8-1.5g: 25-35g; The ratio of the second modified nano-silica, deionized water, and aluminum chloride in A3 is 250-300g: 600-700ml: 12-18g.
5. The insulating tape for new energy batteries according to claim 1, characterized in that: The modified polyimide resin is prepared using the following specific steps: B1. Add N,N-dimethylformamide to a four-necked flask, and under nitrogen protection, add m-phenylenediamine and 4,4'-diaminodiphenyl ether. Stir at 400 r / min until dissolved, and control the temperature at 0-5℃. Add pyromellitic dianhydride in 3-4 portions, stirring for 30-40 min after each addition. After the viscosity of the system reaches 5000-8000 mPa·s, continue stirring and reacting for 2-3 h to obtain a copolymer polyamic acid solution. B2. Add xylene to the copolymerized polyamic acid solution and stir at 500 r / min to form a mixed system; add maleic anhydride and dicumyl peroxide, and heat to 85-95℃ under nitrogen protection, stirring and refluxing for 4-5 h; after the reaction is completed, heat to 120-130℃ and stir at 300 r / min for imidization for 2-3 h to complete the imidization process; after cooling to room temperature, filter, wash 3 times with xylene, and then vacuum dry at 120-130℃ for 6-8 h to obtain the grafted modified polyimide resin; B3. Take the grafted modified polyimide resin and add a 3:1 volume ratio of ethanol / butanone mixed solvent. Stir at 400 r / min until dissolved. Add epoxy resin E-51 and triethylenetetramine. Stir at 500 r / min until homogeneous, then heat to 60-70℃ and stir for 3-4 hours. During this period, take a sample every 1 hour to measure the gel time. Stop the reaction when the gel time stabilizes at 30-40 minutes. Pour the solution into water to precipitate, filter, wash 3 times with ethanol, and vacuum dry the precipitate at 130-140℃ for 7-9 hours to obtain the modified polyimide resin.
6. The insulating tape for new energy batteries according to claim 5, characterized in that: The ratio of N,N-dimethylformamide, m-phenylenediamine, 4,4'-diaminodiphenyl ether, and pyromellitic dianhydride in B1 is 200-250ml: 30-40g: 15-20g: 40-50g; The ratio of the amount of the copolymer polyamic acid solution, xylene, maleic anhydride, and dicumyl peroxide in B2 is 300-350ml: 500-600ml: 8-12g: 0.5-1g; The ratio of grafted modified polyimide resin, ethanol / butanone mixed solvent, epoxy resin E-51, and triethylenetetramine in B3 is 120-150g: 400-500ml: 15-20g: 2-3g.
7. A method for preparing insulating tape for new energy batteries, characterized in that: Specifically, it includes the following steps: S1. Place the fiberglass cloth in deionized water and stir at 300 r / min for 15 min to remove surface dust and loose fibers. Drain the cloth. Transfer it to a 5%-8% sodium hydroxide solution and stir at 200 r / min for 20 min at 60-70℃ to activate the cloth surface. Wash with deionized water until the pH is neutral. Then dry in an oven at 120-130℃ for 2-3 hours and cool for later use. S2. Take the modified polyimide resin and epoxy resin E-51, add them to the ethanol / butanone mixed solvent, and stir at 400-600 r / min at 50-60℃ until the resin is completely dissolved to form a clear and transparent resin liquid. S3. Take modified nano-silica, add ethanol / butanone mixed solvent and silane coupling agent KH-550, stir at 800r / min for 15min, and then ultrasonically disperse for 10-15min for pretreatment. Then, the pretreated modified nano-silica was slowly added to the resin liquid of S2 while stirring at 1000-1200 r / min. After the addition was complete, the stirring was continued at high speed for 25-35 min. Then, the mixture was transferred to an ice-water bath and ultrasonically dispersed for 20-30 min to ensure that the nano-silica did not agglomerate. S4. Add polydimethylsiloxane and paraffinic mineral oil to the S3 dispersion system, adjust the stirring speed to 300-400 r / min, and stir at room temperature for 15-25 min to ensure uniform dispersion of the additives. Introduce nitrogen gas, slowly add triethylenetetramine to the system, and stir at 300-400 r / min for 15-20 min to ensure that the curing agent is completely integrated and there are no obvious particles or stratification. S5. Filter the prepared coating through an 800-1000 mesh nylon filter. Let the filtered coating stand at room temperature for 30-60 minutes to naturally remove the residual micro bubbles in the system, and obtain an insulating tape coating that can be used for coating. S6. Lay the pretreated fiberglass cloth flat on the conveyor belt of the coating machine, and evenly coat both sides of the cloth with the above coating, with a coating thickness of 0.05-0.1mm. After coating, send the substrate into the drying oven and process it according to the step curing procedure: first dry at 90-95℃ for 25-35min, then raise the temperature to 125-135℃ for 55-65min, and finally raise the temperature to 175-185℃ for 110-130min to fully complete the curing reaction, ensuring the tape's high temperature resistance and electrolyte resistance, and obtain the insulating tape for new energy batteries.
8. The method for preparing an insulating tape for new energy batteries according to claim 7, characterized in that: The temperature of the ice-water bath environment in S3 is controlled at 0-5℃, the ultrasonic dispersion power is 300-500W, and the stirring is performed once every 5 minutes during the ultrasonic process, with each stirring lasting 30 seconds.
9. The method for preparing an insulating tape for new energy batteries according to claim 7, characterized in that: The coating speed of the coating machine in S6 is 1-2 m / min. During the coating process, hot air is used for assisted drying. The hot air temperature is 40-50℃ and the hot air speed is 1-1.5 m / s to prevent uneven thickness of the coating due to sagging during the coating process, and at the same time, to initially remove some of the solvent.
Citation Information
Patent Citations
Preparation method of epoxy-based thermal-conductive insulating composite adhesive film
CN110184008A
Thermosetting resin composition, epoxy resin material, composite material of epoxy resin material and preparation method of composite material
CN115746223A
Insulating material with corrosion resistance and production process thereof
CN120484443A
Polymer-based paint and application thereof as well as polymer-based coating and application thereof
CN120484613A
Cited By
Corrosion-resistant polymer composite waterproof coating and preparation method thereof
CN121406202A
Adhesive tape for battery insulation and compounding process thereof
CN121406250A
Special adhesive tape for high-voltage-resistant capacitor
CN122326127A